2021
DOI: 10.1016/j.ekir.2021.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Molidustat for Japanese Patients With Renal Anemia Receiving Dialysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 21 publications
1
38
0
Order By: Relevance
“…The proportion of patients with Hb levels in the target range decreased from baseline to Week 6, with a corresponding rise in the proportion of patients with Hb level below the target range. These observations are consistent with the onset of effect of molidustat of 6–8 weeks observed in the MIYABI ND‐M and HD‐M studies, as well as in phases 1 and 2 studies conducted in white and Asian patients (REF to MIAYBI ND‐M and HD‐M) ( 16 , 18 , 24 , 25 ). These adjustment phases observed for Hb level and for the proportion of patients with Hb levels in the target range are most likely a reflection of the time needed to reach an optimal molidustat dosage.…”
Section: Discussionsupporting
confidence: 89%
“…The proportion of patients with Hb levels in the target range decreased from baseline to Week 6, with a corresponding rise in the proportion of patients with Hb level below the target range. These observations are consistent with the onset of effect of molidustat of 6–8 weeks observed in the MIYABI ND‐M and HD‐M studies, as well as in phases 1 and 2 studies conducted in white and Asian patients (REF to MIAYBI ND‐M and HD‐M) ( 16 , 18 , 24 , 25 ). These adjustment phases observed for Hb level and for the proportion of patients with Hb levels in the target range are most likely a reflection of the time needed to reach an optimal molidustat dosage.…”
Section: Discussionsupporting
confidence: 89%
“…The endogenous EPO levels induced during treatment were close to the normal physiologic range of EPO, which proved its efficacy was non-inferior to ESAs (Akizawa et al, 2019c;Macdougall et al, 2019;Akizawa et al, 2021b). Molidustat has been shown to increase the availability of iron metabolism by the observation of changes in laboratory parameters (Macdougall et al, 2019), while the non-dropped levels of cholesterol and increasing levels of CRP may indicate a question of its safety (Akizawa et al, 2021b). In animal models, molidustat was shown to be effective in renal and inflammatory anemia, and unlike ESA therapy, it reduced blood pressure in an adenine-induced CKD model (Li L. et al, 2020).…”
Section: Molidustat (Bay 85-3934)mentioning
confidence: 65%
“…Several phase 3 studies reported a good response of molidustat in Japanese patients with renal anemia who were not treated with dialysis and who were undergoing hemodialysis or peritoneal dialysis (Macdougall et al, 2019;Yamamoto et al, 2019;Yamamoto et al, 2021). The endogenous EPO levels induced during treatment were close to the normal physiologic range of EPO, which proved its efficacy was non-inferior to ESAs (Akizawa et al, 2019c;Macdougall et al, 2019;Akizawa et al, 2021b). Molidustat has been shown to increase the availability of iron metabolism by the observation of changes in laboratory parameters (Macdougall et al, 2019), while the non-dropped levels of cholesterol and increasing levels of CRP may indicate a question of its safety (Akizawa et al, 2021b).…”
Section: Molidustat (Bay 85-3934)mentioning
confidence: 95%
See 1 more Smart Citation
“…Molidustat/BAY85-3934) but vadadustat and others (i.e. Roxadustat/FG-4592, Daprodustat/GSK1278863, Enarodustat/JTZ-951) do not (Brigandi et al, 2016;Holdstock et al, 2016;Akizawa et al, 2019;Akizawa et al, 2021) is an area for future studies. The observation that HIF-PHIs are erythropoietic at doses that do not stimulate VEGF also warrants investigation.…”
Section: Discussionmentioning
confidence: 98%